THE DEVELOPMENT ISSUES OF CROSS-BORDER E-COMMERCE IN RUSSIA - A. I. Yakovlev; A. V. Smirnov (Дискурс, 2016)
The article analyzes the main trends of the development of cross-border e-commerce, presents the position of the main characters: both supporters of «free trade» and protectionism on issues such as government regulation, as well as further development of cross-border e-commerce.